Analisis Pengungkapan Lingkungan Perusahaan Go Publik di Indonesia - Hendrajaya, Hendrajaya (STIE Widya Manggala, 2008)
This research has the purpose to review the relation among company size with environmental information disclosure to analyze environmental disclosure go public companies in Indonesia. The sample is taken from 98 go public companies in Jakarta Stock Exchange, divided in two categories were high profile industry and low profile industry. The result of correlation value examine shows that there is relation between company size and company environmental information disclosure. The conclusion is the biggest companies in Indonesia more disclose environmental information. The second hypothesis examnitaio0n information. The second hypothesis examination was result to refuse Ho and offer Ha. The conclusion was taken that high profile industry companies more reports environmental information better more low profile industry companies.